ANALYSIS OF SIMFAKUM ACCEPTANCE USING THE TAM AND WEBQUAL METHOD - Fahril, Muhammad; Megawati, Megawati; Fronita, Mona; Rahmawita, Medyantiwi (Informatika, Universitas Jenderal Soedirman, 2024)
The Faculty of Law, Riau Islamic University implements an Information System that can support and assist students in writing correspondence for student needs and is named the Faculty of Law Management Information System or abbreviated and known as SIMFAKUM. From the results of observations and interviews with several students and SIMFAKUM Admin, it is known that there were complaints or problems experienced by users during the implementation of SIMFAKUM. Based on previous research, TAM and Webqual can be used together to measure information system acceptance. The research was conducted with the aim of obtaining the acceptance level of UIR Law Faculty students towards SIMFAKUM based on the TAM and WEBQUAL methods as well as producing recommendations to the UIR Law Faculty with the results of the analysis of student acceptance levels towards SIMFAKUM. For sampling, Simple Random Sampling was used for students at the Faculty of Law, Islamic University of Riau as SIMFAKUM users with a total of 95 respondents. Data processing techniques use Structural Equation Model (SEM) and Partial Least Squres (PLS) with Smart-PLS 3.0 software. There are 6 hypotheses in this research and 5 hypotheses are accepted while 1 hypothesis is rejected, therefore SIMFAKUM needs to improve and improve features to support student needs in correspondence matters.